2014
DOI: 10.3747/co.21.1729
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Unmet Needs of Rural and Aboriginal Cancer Survivors in Northern British Columbia

Abstract: Background: The unmet needs of cancer survivors in rural, remote, and aboriginal communities are largely unexplored. We explored potential differences between rural survivors (rss) in 4 general population (gp) and 4 First Nations (fn) communities. Methods: We approached 4 gp and 4 fn rs communities to participate in a mixed-methods project. Participants completed the Hospital Anxiety and Depression Scale (hads) and the Survivor Unmet Needs Survey (suns) and provided demographic information. Each question on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…For example, So et al (2014) have demonstrated health and information had the highest frequency among unmet needs domain and the second one belonged to work and financial concerns( 17 ). Olson et al (2014) had the same findings, and in a context of rural and urban samples, the most common unmet needs had been information ( 18 ). In another study Edib et al (2016) illustrated psychological domain is the most mentioned needs, followed by physical, patient care needs, health information and the lowest was sexuality domain ( 19 ).…”
Section: Discussionmentioning
confidence: 81%
“…For example, So et al (2014) have demonstrated health and information had the highest frequency among unmet needs domain and the second one belonged to work and financial concerns( 17 ). Olson et al (2014) had the same findings, and in a context of rural and urban samples, the most common unmet needs had been information ( 18 ). In another study Edib et al (2016) illustrated psychological domain is the most mentioned needs, followed by physical, patient care needs, health information and the lowest was sexuality domain ( 19 ).…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, in the review study on cancer sufferers (i.e., breast, lung, prostate, colorectal, and cervix) in Nigeria, Okediji et al found the highest needs in the information-health system, as well as psychological and physical-everyday life domains (20). Furthermore, Olson et al, as well as Park et al referred to the patients' need for information about their disease as the most unmet need in both urban and rural patients (21,12). Moreover, Moradi et al highlighted the information needs as the most significant need of females with breast cancer in Tabriz, Iran (22) while Uchida et al reported information-health and psychological needs as the most important needs of women with breast cancer (11).…”
Section: Discussionmentioning
confidence: 99%
“…Participants' stories about residential schools and differential treatment within clinics suggest that there are colonial foundations to their silence and fatalism that are still in operation. For example, the remoteness of many communities in Canada, which severely limits access to health care, education, and many other forms of social support, stems directly from Canadian policies of land dispossession and displacement. Furthermore, Indigenous health continues to be impacted by ongoing neglect of federal responsibilities signed in treaties and land agreements, such as ensuring equitable access to healthcare, education, and housing…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during treatment, First Nations and Métis patients face significantly higher distress scores for pain, depression, anxiety, and shortness of breath than Caucasian patients . Rural First Nations cancer survivors show significantly higher levels of anxiety and higher unmet needs in all categories of an unmet needs survey than non–First Nations rural survivors . These differences may be attributed somewhat to widespread perceptions and beliefs within First Nations communities that cancer is a death sentence .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation